Plan de marketing internacional para la microempresa Hidrogen System - Jurado, Wilson S. (2019)
The present project called “INTERNATIONAL MARKETING PLAN FOR MICRO ENTERPRISE HIDROGEN SYSTEM aims to present an alternative solution that is focused on the diversification of new markets for its products and with it the increase in sales. This plan was developed based on two areas, bibliographic and field research. As for the first, it has to do with all the theoretical foundations related to: definitions, objectives, characteristics, classification and structure of each of the components of the marketing plan. The second refers to the application of 95 surveys to micro enterprise customers and to observation visits to the company. The results obtained in the surveys allowed us to identify that the client is satisfied in terms of the care he provides, as well as the punctuality in the delivery and the quality of the service and the product he offers. Likewise, the negative aspects were identified: lack of promotion through technological tools, the same ones that served to formulate the proposal. Regarding the methodology used, the methods, inductive, deductive and analytical were applied and as techniques the survey, interview and observation were applied. Therefore, the proposed marketing plan is aimed at presenting the product within the Colombian market, improving its corporate image to its customers and its environment, increasing promotions and the application of new advertising strategies where priority is given to the use of communication technologies. At the end is the conclusions, recommendations, bibliography and annexes